2011
DOI: 10.5012/bkcs.2011.32.10.3793
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Ag2O Microstructures from Cubes to Octapods and Their Antibacterial Activities

Abstract: The selective synthesis of inorganic oxides with unique morphology has attracted considerable interest because of their morphology-dependent properties and applications. 1-3Efforts on most synthetic inorganic oxides have been focused on preparing a stable morphology rather than providing a strategy for producing various morphologies. Therefore, well-controlled methods for synthesizing inorganic oxides with a systematic evolution of morphology should be developed by adjusting the experimental conditions. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It can be observed that the control sample showed the crystalline peaks at Bragg angle (2θ) 32.72°, 37.95°, 54.78°, 65.28° and 68.6° which were attributed to the crystalline planes (111), (200), (220), (311), and (222) according to Joint committee on powder diffraction standards (JCPDS) file no. 12-0793 [18]. The treated sample also exhibited the similar peaks at Bragg angle 32.72º, 37.97º, 54.78º, 65.31º, and 68.59º.…”
Section: Xrd Studysupporting
confidence: 52%
“…It can be observed that the control sample showed the crystalline peaks at Bragg angle (2θ) 32.72°, 37.95°, 54.78°, 65.28° and 68.6° which were attributed to the crystalline planes (111), (200), (220), (311), and (222) according to Joint committee on powder diffraction standards (JCPDS) file no. 12-0793 [18]. The treated sample also exhibited the similar peaks at Bragg angle 32.72º, 37.97º, 54.78º, 65.31º, and 68.59º.…”
Section: Xrd Studysupporting
confidence: 52%
“…The final solution was stirred for 20 min and incubated for 4 h at room temperature. The synthesis of cubic Ag 2 O has been reported previously . In a typical synthesis of cubic Ag 2 O, a mixed solution of water (994.2 mL), 0.1 M AgNO 3 aqueous solution (2.5 mL), and pyridine (0.848 mL) was prepared, and then a 1.0 M NaOH aqueous solution (2.5 mL) was quickly added to the mixed solution.…”
Section: Methodsmentioning
confidence: 99%
“…Different Ag 2 O morphologies containing cubic structures were prepared based on an Ag–pyridine complex solution, where pyridine acts as the ligand for Ag + ions. Ag 2 O was obtained by the reaction of Ag–pyridine complex in the base media (Figure H) . Several reports concerning the fabrication of Ag cubic structures have been published (Figure I) …”
Section: Controlled Morphology Of Ag Npsmentioning
confidence: 99%